2012
DOI: 10.1111/j.1747-4949.2012.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Refusal of Thrombolytic Therapy for Suspected Acute Ischemic Stroke

Abstract: Objective To determine factors associated with patients refusing IV t-PA for suspected acute ischemic stroke (AIS), and to compare the outcomes of patients who refused t-PA (RT) with those treated with t-PA. Methods Patients who were treated with and refused t-PA at our stroke center were identified retrospectively. Demographics, clinical presentation, and outcome measures were collected and compared. Clinical outcome was defined as excellent (mRS: 0–1), good (mRS: 0–2), and poor (mRS: 3–6). Results Over 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Of the cases presented in our study, the patients who refused the fibrinolytic treatment invoked the fear of hemorrhagic risk. In the hospital where all the cases were registrated, we found a decline rate of approximately 2% over the study period, a smaller percentage compared to those reported by other studies [35]. We have also found that there has been a downward trend in refusal over the last few years.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Of the cases presented in our study, the patients who refused the fibrinolytic treatment invoked the fear of hemorrhagic risk. In the hospital where all the cases were registrated, we found a decline rate of approximately 2% over the study period, a smaller percentage compared to those reported by other studies [35]. We have also found that there has been a downward trend in refusal over the last few years.…”
Section: Discussionsupporting
confidence: 43%
“…We have also found that there has been a downward trend in refusal over the last few years. The experience accumulated by physicians over time (both in conducting the thrombolysis procedure and in relation to patients or their legal representatives), the results obtained and the recent scientific evidence that reported t-PA safety for patients with mild symptoms too [36] may influence positively the doctors’ behavior and, implicitly, the increase of patients’ confidence in the benefits of this specific therapy [35]. Also, the recent efforts of the Ministry of Health to raise awareness among the public about the alarming signs of ischemic stroke, showing the benefits of thrombolysis, and the need for treatment may be associated with this decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The observed prevalence of tPA declination in this national cohort is less than previously reported in single-center or regional studies (4.2%-7.5% declined tPA). 10,15,16 This may be due to an overestimation of treatment declination in smaller sample cohorts, the impact of national efforts to improve tPA use among GWTG-Stroke participating hospitals, or underlying regional variation in declining tPA across the country. 10 Despite the lower overall prevalence of tPA declination, the current study provides further evidence in support of previous observations that non-Hispanic Black patients with AIS are more likely to decline tPA than non-Black patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in patients presenting with an NIHSS score <15, lower NIHSS score was associated with a greater risk of tPA declination, consistent with other published reports. 10,15 Patients with minor deficits may perceive risks of disability differently from patients with more debilitating deficits, and this perception may affect decision-making about treatment with tPA. Declining care was also more likely in patients with very severe stroke (NIHSS score >15).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed that patients with atrial fibrillation or greater stroke severity were more likely to use the EMS. For these patients, the neurologist evaluation (Vahidy, Rahbar, Lal, Grotta, & Savitz, 2015) and the patients’ caregivers’ concerns about the risk of thrombolysis may cause delays for treatment. Standardized training has been implemented to teach clinicians to be more persuasive when educating patients and caregivers regarding the importance of timely intervention for stroke.…”
Section: Discussionmentioning
confidence: 99%